INSIDENSI PENGGEREK BATANG PADI KUNING (Schirpophaga incertulas Walker) PADA TIGA VARIETAS PADI : KASUS DI DESA KEMUMU BENGKULU UTARA - Irma Cahyoko; Dwinardi Apriyanto; Kanang S. Hindarto (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2018)
[INCIDENCE OF THE RICE YELLOW STEM BORER (Schirpophaga incertulas Walker) ON THREE RICE VARIETIES IN KEMUMU, NORTH BENGKULU]. Rice yellow stem borer (RYSB), Schirpophaga incertulas Walker, often causes yield loss in irrigated rice field. Dead heard and white ear head are the common symptomps resulted from the larval damage. The use of resistant varieties may reduce the risk of yield loss, but the resistance may lose quickly as the varieties are continually grown in a large area. The assessment of the insect incidence in rice field is necessary in order to determine the status of the pest for certain period of time. The objective of the study was to determine the incidence and damage incurred by RYSB in three rice varieties, Mekongga, Cibogo, and Situ Bagendit at farmer rice fields. A survey was conducted in December 2017-February 2018 in Kemumu, North Bengkulu Regency. Observation of RYSB was made on randomly selected 30 hills from + 1 ha area for each variety that was located adjacent to each other. Grain yield was measured from the sampled hills and from 3 plots of 9 m2 . Weight of 1000 grain was measured from grain of three sampled hills. The results revealed that the incidence of RYSB was low, as indicated by the presence of egg mass and larvae of RYSB, and no significant difference was found among the three varieties. Nevertheless, the average cumulative number and percentage of dead heart and white ear head was significantly lower in Mekongga than those of Cibogo and Situ Bagendit. In term of grain yield, however, Mekongga outperformed the other two varieties. The low incidence of RYSB might suggest that growing different variety practiced by local farmers was able to suppress pest population, and therefore it should be implemented in all main areas of rice production.